Macrophage Activation Syndrome: A Potentially Fatal Complication of Kawasaki Disease - Kallol BOSE; Sudip SAHA; Prabir SAHA; Piyasi MONDAL (Archives of Rheumatology, 2015)
Kawasaki disease is an acute vasculitis of childhood. Macrophage activation syndrome is a rare life threatening complication. In this article, we report a five-year-six-month old girl patient with Kawasaki disease who developed irritability, hepatosplenomegaly, and pancytopenia after treatment with intravenous immunoglobulins. Patient’s blood test and bone marrow aspiration results suggested macrophage activation syndrome. The patient responded to dexamethasone in a dose of 10 mg/m2/day.